BERKENALAN DENGAN DASAR ETIS ETIKA BISNIS MENURUT ETIKA EMMANUEL LEVINAS - Weruin, Urbanus Ura (Jurnal Bakti Masyarakat Indonesia, 2024)
The development of information technology and economic globalization are changing perceptions, practices and core values in business. It is increasingly realized that the priority of business is not just seeking personal or corporate profit by any means necessary but rather must adhere to ethical business principles. A number of parties are calling for the spectrum of business ethics to be broadened and its application to be radical because future economic practices do not just require conventional business ethics but rather radical, relevant, reflective and brilliant models of business ethics. A model of business ethics that has a new perspective; a model of business ethics that appreciates multiple points of view; a business ethics model that injects critical awareness so that business people have autonomous ethical awareness. Levinas's ethical thinking was chosen as a frame of reference in introducing business ethics in this PKM because radical. For Levinas, business ethics is not a choice but an ethical obligation that is absolute and asymmetrical. Ethics originates from moral demands for every human being. But the moral basis is not in each individual or corporation but in others, in the environment, in society at large. That morally every person and every company has an ethical responsibility to be responsible for the needs and interests of other people. This kind of ethical demand is called radical because it places ethical weight not on individuals or corporations but on Others who are outside individuals and corporations. This PKM was carried out together with PT. Crown Pratama as partner. The aim of this PKM is to broaden the understanding of PKM partner staff and employees about the importance of business ethics and its application in business practices. Business ethical values such as honesty, fairness, responsibility and the interests of society as a whole cannot be defeated for personal or corporate gain. The results of this PKM show that 75.6% said they were able to understand and be useful for individuals and corporations. ABSTRAK Perkembangan teknologi informasi dan globalisasi ekonomi mengubah persepsi, praktik, dan nilai-nilai utama dalam bisnis. Sejumlah pihak menyerukan agar spektrum etika bisnis diperluas dan penerapannya perlu radikal karena praktik ekonomi masa depan tidak sekadar membutuhkan etika bisnis konvensional melainkan model etika bisnis yang radikal, relevan, reflektif, dan brilian. Sebuah model etika bisnis yang memiliki cara pandang baru; sebuah model etika bisnis yang mengapresiasi banyak sudut pandang; sebuah model etika bisnis yang menginjeksi kesadaran kritis agar para pelaku bisnis memiliki kesadaran etis yang otonom. Pemikiran etika Levinas dipilih sebagai kerangka acuan dalam memperkenalkan etika bisnis dalam PKM ini secara radikal. Bagi Levinas, etika bisnis bukan sebuah pilihan melainkan sebuah kewajiban etis yang bersifat mutlak dan asimetris. Tetapi dasar moral tersebut bukan pada diri masing-masing individu atau korporasi melainkan pada Yang Lain, pada lingkungan, padamasyarakat luas. Bahwa secara moral setiap orang dan setiap perusahaan memiliki tanggung jawab etis untuk bertanggungjawab atas kebutuhan dan kepentingan orang lain. Tuntutan etis semacam ini disebut radikal karena meletakkan bobot etis tidak pada individu atau korporasi melainkan pada Yang Lain yang berada di luar individu dan korporasi. PKM ini dilakukan bersama PT. Crown Pratama sebagai mitra. Tujuan PKM ini adalah memperluas pemahaman para staf dan karyawan mitra PKM tentang pentingnya etika bisnis dan penerapannya dalam praktik berbisnis. Nilai-nilai etika bisnis seperti kejujuran, keadilan, tanggung jawab, dan kepentingan masyarakat secara keseluruhan tidak bisa dikalahkan demi keuntungan personal atau perusahaan. Hasil PKM ini menunjukkan bahwa 75,6% menyatakan mampu memahami dan berguna bagi individu dan korporasi.